2013
DOI: 10.1037/a0026385
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependant behavioral strategies in a visual search task in baboons (Papio papio) and their relation to inhibitory control.

Abstract: A computerized visual search task was presented to 18 guinea baboons (Papio papio) ranging from 2.7 to 14.3 years of age. The task, inspired from Hick’s (1952) task, required detection of a target among a variable number of distractors equidistant to a start button. The reaction times (RTs) and movement times both increased with the number of distractors expressed in bits of information. However, the slope of RT per bit function correlated positively with age, whereas a negative correlation was found for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
2
9
1
Order By: Relevance
“…Age variations in performance were similar between the TI task and in an adaptation of the Wisconsin Card Sorting Task (WCST) measuring cognitive flexibility (Bonté et al, 2011 ). This contrasts previous results from a task requiring motor inhibitory control (Fagot et al, 2011 ). Therefore, these findings suggest that cognitive flexibility was a central component of the cognitive system that evolved within non-human primates.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Age variations in performance were similar between the TI task and in an adaptation of the Wisconsin Card Sorting Task (WCST) measuring cognitive flexibility (Bonté et al, 2011 ). This contrasts previous results from a task requiring motor inhibitory control (Fagot et al, 2011 ). Therefore, these findings suggest that cognitive flexibility was a central component of the cognitive system that evolved within non-human primates.…”
contrasting
confidence: 99%
“…This effect is clearly demonstrated in Fagot et al (2011; Experiment 2). In this study, baboons of different ages had to inhibit ongoing manual pointing toward a target stimulus as a consequence of a change in target location.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Such difficulties to switch to former unrewarded stimuli, rather than inability to overcome inhibition, have also been suggested by Powers (1989) . Bonté, Kemp, and Fagot (2014) have suggested that inhibitory control and cognitive flexibility might involve different cognitive processes, since studies on age-dependent advancements of inhibitory control ( Fagot, Bonté, & Hopkins, 2013 ) contradict age-related decline in cognitive flexibility ( Bonté, Flemming, & Fagot, 2011; Bonté et al., 2014 ). Furthermore, since the age-dependent patterns in a reversal learning task ( Bonté et al., 2014 ) resembled those in the Wisconsin Card Sorting Task ( Bonté et al., 2011 ), Bonté et al.…”
Section: Discussionmentioning
confidence: 99%
“…Research with monkeys trained to perform visual search tasks has been useful for distinguishing the neural systems associated with controlled versus data‐driven attention scanning . Behavioral research with nonhuman primates using the visual‐search paradigm has also been informative, indicating the spatial or object‐based information used to guide attention (e.g., Refs ), the role of inhibitory control, and the consequences of competition between bottom–up and top–down search cues . For example, how is search performance affected when there is a singleton, pop‐out distractor stimulus in the array?…”
Section: Executive Attentionmentioning
confidence: 99%